IMPLEMENTASI GERAKAN LITERASI SEKOLAH DALAM PENGEMBANGAN MINAT MEMBACA DAN MENULIS SISWA KELAS IV DI SDN NGAWI PURBA 2 - TEJA INSYAF SUKARIYADI; WIKANSO WIKANSO; WAHYUNINGSIH WAHYUNINGSIH (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2023)
The implementation of the School Literacy Movement (GLS) program is expected to be able to develop students' interest in reading and writing. This study aims to 1) determine the implementation of the School Literacy Movement in developing students' interest in reading and writing at SDN Ngawi Purba 2, and 2) find out the obstacles to implementing GLS at SDN Ngawi Purba 2. This type of research is descriptive qualitative. The subjects of this study were school principals, class teachers, and students. The research object is the implementation of the School Literacy Movement in developing students' interest in reading and writing which includes the habituation stage, the development stage and the learning stage. The method used in collecting data is in the form of interviews, observation, and documentation. The data analysis method uses the steps proposed by Miles and Huberman through data reduction, data presentation, conclusion and verification. The results of this study indicate that SDN Ngawi Purba 2 is a school that implements the GLS program. Students are required to read 15 minutes before learning begins. This program is in accordance with the policy rolled out starting in March 2016 by the Directorate General of Primary and Secondary Education of the Ministry of Education and Culture. SDN Ngawi Purba 2 hopes that by running this program the school will have a culture that will continue to be preserved. GLS is important to implement in order to develop students' interest in reading and writing. ABSTRAKPelaksanaan program Gerakan Literasi Sekolah (GLS) diharapkan mampu mengembangkan minat membaca dan menulis siswa. Penelitian ini bertujuan untuk 1) mengetahui implementasi Gerakan Literasi Sekolah dalam mengembangkan minat membaca dan menulis siswa di SDN Ngawi Purba 2, dan 2) mengetahui hambatan implementasi GLS di SDN Ngawi Purba 2. Jenis penelitian ini adalah kualitatif deskriptif. Subjek penelitian ini adalah kepala sekolah, guru kelas, dan peserta didik. Objek penelitian berupa implementasi Gerakan Literasi Sekolah dalam pengembangan minat membaca dan menulis siswa yang meliputi tahap pembiasaan, tahap pengembangan dan tahap pembelajaran. Metode yang digunakan dalam mengumpulkan data berupa wawancara, observasi, dan dokumentasi. Metode analisis data dengan langkah-langkah yang dikemukakan oleh Miles dan Huberman melalui reduksi data, penyajian data, kesimpulan dan verifikasi. Hasil penelitian ini menunjukkan bahwa SDN Ngawi Purba 2 merupakan sekolah yang menerapkan program GLS. Siswa diwajibkan untuk membaca 15 menit sebelum pembelajaran dimulai. Program ini sesuai dengan kebijakan yang digulirkan mulai Maret 2016 oleh Direktorat Jendral Pendidikan Dasar dan Menengah Kemendikbud. SDN Ngawi Purba 2 berharap dengan menjalankan program ini sekolah mempunyai budaya yang terus dilestarikan. GLS penting untuk dilaksanakan guna mengembangkan minat membaca dan menulis siswa.